ANALISIS GAYA BAHASA PADA LIRIK LAGU MELAYU PONTIANAK ALBUM UNTO MU PONTIANAK KARYA HAZAIRIN ACHMAD - Sartika, Dewi; Jupitasari, Mellisa; Syahrani, Agus (Universitas Tanjungpura, 2024)
The purpose of this research is to describe the style of comparative language; conflicting language style; and repetition style; which is in the lyrics of the Malay Pontianak song album Unto Mu Pontianak by Hazairin Achmad. This research uses descriptive qualitative method. The data collection technique uses listening, note taking, and content analysis techniques to interpret the meaning of the message in the song lyrics. Based on the research data analysis of the Malay Pontianak song lyrics of the album Unto Mu Pontianak by Hazairin Achmad it can be concluded: 1) Based on the results of a Comparative Language Style analysis on the Malay Pontianak Song Lyrics of Unto Mu Pontianak Album by Hazairin Achmad found 11 data on Personification style, 8 data on Metaphor style , 3 data on Allegorical language style, 5 data on Parable language style, 4 data on Anthesis style, 12 data on Pleonasm style, 3 data on Anticipation language style. 2) Based on the results of analysis of the Conflicting Language Style Analysis on Pontianak Malay Song Lyrics Unto Mu Pontianak Album by Hazairin Achmad found 3 Oksimoron style data, 4 Irony style data, 4 Hyperbole style data, 7 Sarcasm style data, 1 Language style data Sylepsis, 1 Liotes style data, 4 Cynicism style data, 4 Apofasis style data, 2 Apostrophe style data. 3) Based on the results of the analysis of Repetitive Language Style Analysis on Pontianak Malay Song Lyrics Unto Mu Pontianak Album by Hazairin Achmad found 2 Assonasi language style data, 6 tautotes language style data, 2 anaphora language style data, 2 alliteration languagestyle data, 1 language style data epistropha.; and (4) the implementation of learning Indonesian used in this study is in the form of learning media, namely E-Module definitions and types of figures of speech in poetry